Development and validation of dissolution method for carvedilol compression-coated tablets - Ritesh Shah; Sachin Patel; Hetal Patel; Sonia Pandey; Shailesh Shah; Dinesh Shah (Brazilian Journal of Pharmaceutical Sciences, 2011)
The present study describes the development and validation of a dissolution method for carvedilol compression-coated tablets. Dissolution test was performed using a TDT-06T dissolution apparatus. Based on the physiological conditions of the body, 0.1N hydrochloric acid was used as dissolution medium and release was monitored for 2 hours to verify the immediate release pattern of the drug in acidic pH, followed by pH 6.8 in citric-phosphate buffer for 22 hours, to simulate a sustained release pattern in the intestine. Influences of rotation speed and surfactant concentration in medium were evaluated. Samples were analysed by validated UV visible spectrophotometric method at 286 nm. 1% sodium lauryl sulphate (SLS) was found to be optimum for improving carvedilol solubility in pH 6.8 citric-phosphate buffer. Analysis of variance showed no significant difference between the results obtained at 50 and 100 rpm. The discriminating dissolution method was successfully developed for carvedilol compression-coated tablets. The conditions that allowed dissolution determination were USP type I apparatus at 100 rpm, containing 1000 ml of 0.1N HCl for 2 hours, followed by pH 6.8 citric-phosphate buffer with 1% SLS for 22 hours at 37.0 ± 0.5 ºC. Samples were analysed by UV spectrophotometric method and validated as per ICH guidelines. O presente estudo descreve o desenvolvimento e a validação de método de dissolução para comprimidos revestidos de carvedilol. O teste de dissolução foi efetuado utilizando-se o aparelho para dissolução TDT-06T. Com base nas condições fisiológicas do organismo, utilizou-se ácido clorídrico 0,1 N como meio de dissolução e a liberação foi monitorada por 2 horas para se verificar o padrão de liberação imediata do fármaco em condições de pH baixo, seguidas por pH 6,8 em tampão cítrico-fosfato por 22 horas, para simular o padrão de liberação controlada no intestino. Avaliou-se a influência da velocidade de rotação e a concentração de tensoativo no meio. As amostras foram analisadas por método espectrofotométrico UV-visível validado, em 286 nm. O laurilsulfato sódico a 1% (SLS) mostrou-se ótimo para aumentar a solubilidade do carvedilol em pH 6,8 em tampão cítrico-fosfato. A análise da variância não mostrou diferença significativa entre os resultados obtidos a 50 e a 100 rpm. O método da dissolução discriminante foi desenvolvido com sucesso para os comprimidos revestidos de carvedilol. As condições que permitiram a determinação da dissolução foram: aparelho USP tipo I a 100 rpm, contendo 1000 mL de HCL 0,1 N por 2 horas, seguido de pH 6,8 com tampão cítrico-fosfato, com 1% de SLS por 22 horas a 37,0 ± 0,5 ºC. Amostras foram analisadas por método espectrofotométrico e validadas pelas normas ICH.